STRATEGI PENGGUNAAN TEKNOLOGI AUGMENTED REALITY DALAM PEMBELAJARAN SMK - Mulyana Kusandi (CV. ADIBA AISHA AMIRA, 2024)
The application of Augmented Reality (AR) technology in Vocational High School (SMK) learning is becoming increasingly important to prepare students to face the demands of the ever-growing world of work. However, infrastructure constraints, resource availability, and lack of teacher understanding are the main obstacles to effectively integrating AR. This research aims to identify effective strategies in maximizing the potential of AR in vocational school learning and analyze the obstacles that may arise. Suggested strategies include curriculum development integrated with AR, teacher training, infrastructure investment, and cross-sector collaboration. By implementing this strategy, it is hoped that the application of AR in vocational school learning can make a positive contribution to student development and prepare them for an increasingly technological and dynamic world of work.